English Teachers’ Perception and Implementation of Authentic Assessment for Speaking Based on 2013 Curriculum - Mursyida, Isnayani Tabi'ul; Faridi, Abdurrachman; Suwandi, Suwandi (Universitas Negeri Semarang, 2020)
Authentic Assessment is one of important aspects in 2013 Curriculum promoting an idea of assessing students’ authentic skills including speaking. However, many teachers claimed to have difficulties in implementing it properly. This research aims at explaining the English teachers’ perception and implementation of authentic assessment for speaking based on 2013 Curriculum in state senior high schools in Semarang. Descriptive qualitative method is applied in this study. By using purposive sampling technique, sixteen English teachers from sixteen state senior high schools in Semarang were involved. There were four instruments to collect the data, namely questionnaire, interview, document analysis, and classroom observation. The findings of this research revealed that the English teachers had good perception of authentic assessment for speaking both in the concept, preparation and implementation. However, in the actual implementation, it was proven that the teachers did not apply authentic assessment for speaking as required by 2013 Curriculum. This was due to several problems such as limited time, teachers’ lack of creativity, students’ motivation and other reasons. Abstrak Penilaian otentik adalah salah satu aspek penting dalam Kurikulum 2013 yang mempromosikan gagasan tentang penilaian kemampuan otentik siswa, termasuk kemampuan berbicara. Namun, banyak guru yang mengaku mengalami kesulitan dalam mengimplementasikannya. Penelitian ini bertujuan untuk menjelaskan persepsi dan pengimplementasian penilaian otentik untuk kemampuan berbicara berdasarkan Kurikulum 2013 oleh guru bahasa Inggris di sekolah menengah atas negeri di Semarang. Metode deskriptif kualitatif digunakan dalam penelitian ini. Dengan menggunakan teknik purposive sampling, enam belas guru bahasa Inggris dari enam belas sekolah menengah atas negeri di Semarang terlibat. Ada empat instrumen untuk pengumpulan data, yaitu kuesioner, wawancara, analisis dokumen, dan observasi kelas. Temuan penelitian ini mengungkapkan bahwa para guru bahasa Inggris memiliki persepsi yang baik tentang penilaian otentik untuk kemampuan berbicara, baik dalam konsep, persiapan maupun implementasinya. Namun, dalam implementasi aktualnya, terbukti bahwa para guru belum menerapkan penilaian otentik untuk berbicara seperti yang dipersyaratkan oleh Kurikulum 2013. Hal ini disebabkan oleh beberapa masalah yang dihadapi oleh para guru seperti keterbatasan waktu, kurangnya kreativitas guru, motivasi siswa dan alasan-alasan lainnya.